Analisis Kesalahan Mahasiswa dalam Pembuktian Geometri Analitik Materi Segitiga - Anisa Widiastuti; Abi Suwito; Susanto, Susanto (Griya Journal of Mathematics Education and Application, 2023)
The purpose of this research is to find out what mistakes students make in proving a triangle. The research subjects were students in the Analytical Geometry class at the Mathematics Education Study Program at UIN KHAS Jember. This research is a qualitative descriptive study. The data collection techniques used were observation, tests, and interviews. Based on the research results, it was found that the types of errors made by students were (1) errors in the representation of mathematical symbols, (2) errors in the contradiction of triangle inequalities, and (3) errors in writing answers and errors in the proof process